Building Background Knowledge for Academic Achievement - Marzano, Robert J.; Nang Chan Yeema (Alexandria, VA USA ASCD Publications, 2004)
This book shows how a carefully structured combination of two approaches--sustained silent reading and instruction in subject-specific vocabulary terms--can help overcome the deficiencies in background knowledge that hamper the achievement of many children.
Keywords: Adult Nonfiction